1990
DOI: 10.1159/000468719
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Renal Handling of Pancreatic and Salivary Amylase in the Rat

Abstract: Plasma activity and excretion of pancreatic (P) amylase in the rat was found to be negligible. In contrast, the excretion rate of salivary (S) amylase was substantial and variable, depending on diuresis. P-amylase had a higher isoelectric point, a greater sieving coefficient, and a shorter half-life than S-amylase. A bolus injection of 125I-labelled enzymes was followed by the appearance of 125I-labelled enzyme- as well as protein-free 125I activity in the urine. The enzyme loss was smaller and the fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Amylase reabsorption is relatively low: 50% on the aver age [25]. Studies in rats [26] and humans [27,28] have indicated that the FR of both isoenzymes may be differ ent. No data are available on the influence of tubular reab sorption on the IgG and amylase clearance ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Amylase reabsorption is relatively low: 50% on the aver age [25]. Studies in rats [26] and humans [27,28] have indicated that the FR of both isoenzymes may be differ ent. No data are available on the influence of tubular reab sorption on the IgG and amylase clearance ratios.…”
Section: Introductionmentioning
confidence: 99%